Artificial neural networks methods and applications in bio-/neuroinformatics - Koprinkova-Hristova, Petia; Mladenov, Valeri; Kasabov, Nikola K. (Springer International Publishing, 2015)
The book reports on the latest theories on artificial neural networks, with a special emphasis on bio-neuroinformatics methods. It includes twenty-three papers selected from among the best contributions on bio-neuroinformatics-related issues, which were presented at the International Conference on Artificial Neural Networks, held in Sofia, Bulgaria, on September 10-13, 2013 (ICANN 2013).